Volatility, the Macroeconomy, and Asset Prices - BANSAL, RAVI; KIKU, DANA; SHALIASTOVICH, IVAN; YARON, AMIR (Journal of Finance, 2014)
ABSTRACT How important are volatility fluctuations for asset prices and the macroeconomy? We find that an increase in macroeconomic volatility is associated with an increase in discount rates and a decline in consumption. We develop a framework in which cash flow, discount rate, and volatility risks determine risk premia and show that volatility plays a significant role in explaining the joint dynamics of returns to human capital and equity. Volatility risk carries a sizable positive risk premium and helps account for the cross section of expected returns. Our evidence demonstrates that volatility is important for understanding expected returns and macroeconomic fluctuations.